Política ambiental para la conservación de la biodiversidad del campus politécnico de la ESPAM MFL - Calderón Sánchez, Karla Sofía (2019)
Every institution according to the Constitution of the Republic of Ecuador needs to adapt to national policies in environmental aspects, among others. The ESPAM MFL as an academic institution must be a national and regional reference. This research work had as its main objective the development of an environmental policy for the conservation of the polytechnic campus of the ESPFL MFL. Qualitative, bibliographic and participatory methods were used that facilitated strategies to carry out the research, the qualitative and participatory methods allowed to involve the main actors that were the students and teachers; techniques such as the survey and interview with the students of the different careers were also used, which allowed interpreting the knowledge they currently have about biodiversity and its conservation. The Environmental Policy of the ESPAM MFL will be the framework of biodiversity conservation in general, because the guidelines described in it will have to be followed, in order to contribute to the protection of the natural resources found within the campus.